Effect of high hydrostatic pressure treatment on conventional hydroxypropylation of maize starch. (1st August 2016) - Chun, Ei-Hyun; Oh, Seon-Min; Kim, Hui-Yun; Kim, Byung-Yong; Baik, Moo-Yeol
Highlights: Physicochemical properties of hydroxypropylated starches were changed with reaction time. Physicochemical properties were altered by hydroxypropylation with HHP treatment. Hydroxypropylation followed by HHP treatment accelerated substitution. In post-HHP treatment, intra-soluble materials were leached out and granule collapse occurred. Abstract: Effect of high hydrostatic pressure (HHP) treatment on conventional hydroxypropylation of maize starch was investigated. Three groups, 'Con' group (conventional hydroxypropylation), 'HHP-Con' group (HHP treatment before conventional hydroxypropylation), and 'Con-HHP' group (HHP treatment after conventional hydroxypropylation), were used in this work. The degree of substitution (DS) increased over the reaction time in all groups. Swelling power and solubility were high in HHP treated groups compared to Con group because HHP treatment weakens the binding forces inside starch granule. In the results of RVA, the Con-HHP group showed a lower pasting temperature and a higher breakdown and viscosity than the other groups. Pre- and post HHP-treatments altered the physicochemical properties of hydroxypropylated maize starch. Hydrophilic and bulky hydroxypropyl groups may weaken the bindings in the granule, while the HHP treatment promoted the collapse of granules and accelerated the leaching of intra-soluble materials.